The Impact of Malnutrition on the Wound Healing Process: A Summary of Current Knowledge - Rogiński, Miłosz Jan; Liebert, Antoni; Krupiniewicz, Karol; Wojciechowicz, Marek; Brzęcka, Marta; Rogiński, Stanisław; Suchcicki, Mariusz; Chojnowski, Łukasz; Mazurek, Katarzyna; Dominiczak, Anna (Quality in Sport, 2026)
Aim: The aim of this narrative review was to summarize current PubMed-indexed evidence on the impact of malnutrition on the wound healing process and to synthesize clinical data regarding nutritional interventions that may improve wound outcomes. Materials and Methods: A narrative literature review was conducted based exclusively on peer-reviewed studies indexed in PubMed. Experimental studies, observational studies, randomized controlled trials, and systematic reviews addressing nutrition, malnutrition, and wound healing were included. Evidence from the provided publications and their referenced bibliographies was analyzed and synthesized qualitatively. Results: Clinical and experimental evidence shows that malnutrition causes disruptions of all phases of wound healing by disturbing inflammatory control, decreasing collagen deposition, delaying angiogenesis and reducing fibroblast activity. Observational studies report a high prevalence of malnutrition among patients with chronic wounds, particularly pressure injuries and venous leg ulcers, and associate poor nutritional status with slower wound closure and higher complication rates. Randomized clinical trials and systematic reviews indicate that targeted oral nutritional supplementation, especially high-protein formulas enriched with zinc, arginine and antioxidants, improve healing effects in patients with pressure ulcers when they are used as an adjunct to standard wound care.